X-ray spectroscopy and photometry of the long-period polar AI Trianguli with XMM-Newton - Traulsen, I.; Reinsch, K.; Schwarz, R.; Dreizler, S.; Beuermann, K.; Schwope, A. D.; Burwitz, V. (Astronomy and astrophysics (Berlin), 2010)
Context. The energy balance of cataclysmic variables with strong magnetic fields is a central subject in understanding accretion processes on magnetic white dwarfs. With XMM-Newton, we perform a spectroscopic and photometric study of soft X-ray selected polars during their high states of accretion. Aims. On the basis of X-ray and optical observations of the magnetic cataclysmic variable AI Tri, we derive the properties of the spectral components, their flux contributions, and the physical structure of the accretion region in soft polars. Methods. We use multi-temperature approaches in our xspec modeling of the X-ray spectra to describe the physical conditions and the structures of the post-shock accretion flow and the accretion spot on the white-dwarf surface. In addition, we investigate the accretion geometry of the system by completing a timing analysis of the photometric data. Results. Flaring soft X-ray emission from the heated surface of the white dwarf dominates the X-ray flux during roughly 70% of the binary cycle. This component deviates from a single black body and can be described by a superimposition of mildly absorbed black bodies with a Gaussian temperature distribution between kTbb,low := 2 eV and kTbb,high eV, and NH,ISM $= 1.5^{+0.8}_{-0.7}$ × 1020 cm-2. In addition, weaker hard X-ray emission is visible nearly all the time. The spectrum from the cooling post-shock accretion flow is most closely fitted by a combination of thermal plasma mekal models with temperature profiles adapted from prior stationary two-fluid hydrodynamic calculations. The resulting plasma temperatures lie between kTMEKAL,low $= 0.8^{+0.4}_{-0.2}$ keV and kTMEKAL,high $= 20.0^{+9.9}_{-6.1}$ keV; additional intrinsic, partial-covering absorption is on the order of NH,int $= 3.3^{+2.5}_{-1.2}$× 1023 cm-2. The soft X-ray light curves show a dip during the bright phase, which can be interpreted as self-absorption in the accretion stream. Phase-resolved spectral modeling supports the picture of one-pole accretion and self-eclipse. One of the optical light curves corresponds to an irregular mode of accretion. During a short XMM-Newton observation at the same epoch, the X-ray emission of the system is clearly dominated by the soft component.